Accessing Genetic Information with Liquid Biopsies. Issue 10 (October 2015) - Cai, Xuyu; Janku, Filip; Zhan, Qimin; Fan, Jian-Bing
Abstract : Recent scientific advances in understanding circulating tumor cells, cell-free DNA/RNA, and exosomes in blood have laid a solid foundation for the development of routine molecular 'liquid biopsies'. This approach provides non-invasive access to genetic information – somatic mutations, epigenetic changes, and differential expression – about the physiological conditions of our body and diseases. It opens a valuable avenue for future genetic studies and human disease diagnosis, including prenatal and neurodegenerative disease diagnosis, as well as for cancer screening and monitoring. With the rapid development of highly sensitive and accurate technologies such as next-generation sequencing, molecular 'liquid biopsies' will quickly become a central piece in the future of precision medicine. Trends: There will be huge efforts from both academia and industry to develop ultrasensitive and specific methods, including technology platforms, assays, and data analysis tools for (i) circulating cell isolation, manipulation and characterization/analysis, and (ii) circulating nucleic acids analysis. There will be large-scale, well-designed clinical trials to demonstrate the clinical utility of ctDNA/CTC for disease detection and monitoring. There will be continued efforts to integrate knowledge from liquid biopsies into our understanding of health and disease conditions. Non-invasive, liquid biopsy-based diagnostics will be rapidly incorporated into standard healthcare practice and become the central piece in the future precision medicine.